The Spillover Effects of US Unconventional Monetary Policy on the Taiwanese Economy - Chen, Kuan-Chieh (International Journal of Economics and Financial Issues, 2022)
Due to the severity of the 2007-2009 financial crisis, the United States Federal Reserve aggressively lowered the policy rate to zero and adopted several “unconventional” monetary policies, including “Quantitative Easing (QE).” The literature has long suggested that US monetary policies had strong spillover effects on foreign countries. Accordingly, the governor of Taiwan’s central bank, Dr. Fai-Nan Perng, expressed strong concerns about such ripple effects of US policy on the Taiwanese economy. This paper follows Ammer et al. (2016) to use the Federal Reserve’s unconventional monetary policy announcements to support the claim that US monetary policy has significant impacts on the Taiwanese economy and financial markets. Also, the spillover effects of pre-crisis “traditional” monetary policies are compared with the spillover effects from implementing “unconventional” policies during and post-crisis. The results show that US monetary policies exert significant impacts on the Taiwanese economy. Finally, we discuss the response of Taiwan’s central bank to these spillover effects.